Organizational Learning and the Learning Organization - OKOLIE, Ugo Chuks; MEMEH, Ndubuisi Jude (Management Research and Behavior Journal, 2024)
In today's business world, competition is no longer about accumulating resources; rather, the emphasis is on the actual accumulation and utilization of knowledge within the organization. As proposed by this paper, attention has shifted dramatically from acquiring wealth in the organization to an era in which knowledge and learning within the organization become more critical and important to organizational survival and continuous growth. Organizations are legally and corporately recognized entities. They have a reputation, and they can sue and be sued. To that end, this paper contends that organizations can learn, and that the absence or scarcity of an adequate organizational learning culture denies organizations the much-needed competitive edge required to survive and thrive in today's globalized world. The paper examines the technical and social perspectives of organizational learning, arguing that the learning process is context and culture dependent given that effective organizational learning practices improve employee productivity and management performance, it also identifies some barriers to learning, suggests solutions, and concludes that, given the dynamic nature of the business environment in which businesses operate, as well as the rapid changes occurring as a result of technological adoption and innovation, there is an urgent call and need for learning organizations to ensure they secure  intangible performance and not just financial performance to ensure long term sustainability.